(untitled) (Research, Society and Development, 2021)
Water is a necessary asset for all living beings, recognised by the UN as a fundamental right. Thus, public policies play an essential role, both to ensure supply and preservation. Thus, this work sought to understand and analyze the various factors that contribute to drinking water reaching the population. To carry it out, data from bibliographic sources were used, such as scientific articles, discussions on the theme, data from research bodies such as: IBGE, ANA, INPE among others. We noticed the lack of basic sanitation structures in many regions of the country and the population’s lack of awareness about the responsible use of water. We also consider that agricultural and industrial production contributes to the contamination of water through the disposal of waste, pesticides or even chemicals that contaminate the soil, rivers and springs. At the same time anthropic actions such as burning and deforestation have great relevance in environmental conditions and have historically contributed to droughts. The study also indicated that the search for sustainability goes through the environmental conservation of water resources, which despite public policies bringing in their documents laws and guidelines about their use as well as their preservation, we are still far from guaranteeing this asset to future generations, because the culmination of the achievement of these goals goes through the awareness of the population. Conditions that will mitigate the impacts on the environment, seeking sustainable alternatives, an important path to be considered is environmental education that does not occur only in school but throughout society.